System and method of transforming text into image for information hiding - Mahmod, Ramlan; Ahmad Zawawi, Md Nabil; O. K. Rahmat, Rahmita Wirza (2010)
The present invention provides a system and method of transforming text into image for information hiding. The present invention approaches the steganographic problem with respect of a passive warden and it also considering the threats of active attack by active warden to which the robustness of the stego-object is concerned. Accordingly,the present invention provides a system and method of transforming text into image for information hiding which applies cover generation techniques to evade detection, it enables to carry useful amount of information and at the same time survives active attack that can be jeopardized the information it carries.